Núcleos de periódicos e as opiniões de especialistas: estudo na área de educação - Neri, Lidia Alvarenga (1984)
This report is concerned about the work of a core list of periodicals in educational field, chosen by productivity and use in citations and number of requirements of copies of articles presented by the readers of the Center of Bibliographical Informations from MEC-CIBEC. The validity of this core list to specialists in the area was tested through an application form completed by 179 people, specialists in the field and at work in Institutions in the Federal District of Brazil. They were classified into (5) five subgroups: Elementary Teachers; Second Grade Professors; University Professors; Educationists; and Specialists of Educational Administration. The methodology employed to the analysis of the data was based upon Bradford and the Elitism laws, and upon classic quantitative methods, using simple percentage and ranking correlation of orders from Spearman. There were found different levels of knowledge of the periodicals by the subgroups and different correlation coefficients between each subgroup ranking of periodicals and the core list. The second one established by priority of the number of obtained points considering the number of published articles, citations and of the number of required copies -the first one was established by the number of points attributed to each periodicals by the specialists of each subgroup. The results presented different and low levels of knowledge of the core list periodicals, by the subgroups and different and low ranking correlation between the order occupied by the periodicals in the original core list and their positions attributed by the same subgroup, according to the priorities of their specific interest.